Mineralizing activity of periodontal bone tissue of rats with experimental diabetes - Levitsky, A.; Selivanskaya, I.; Tishchenko, T.; Stupak, O. (Journal of Education, Health and Sport, 2023)
Background. To determine the effect of diabetes on the state of periodontal bone tissue. Methods. In rats, diabetes mellitus of the first type (DM1) was reproduced with the help of alloxan and diabetes mellitus of the second type (DM2) with the help of protamine. The activity of alkaline (ALP) and acid (ACP) phosphatases, calcium content, protein and elastase activity were determined in periodontal bone tissue. The level of biochemical markers of inflammation and protective systems was determined in the blood serum and in the gums. The mineralizing activity of bone tissue was determined by the ALP/ACP ratio. Results. It was established that the mineralizing activity of periodontal bones is significantly higher in males and increases with age. The reproduction of DM1 and DM2 in rats caused a significant decrease in the mineralizing activity of periodontal bone tissue and insignificant changes in the level of calcium and protein. In rats with diabetes, an inflammatory process develops in the gums (increase in the level of elastase) against the background of a decrease in the level of markers of protective systems (catalase and lysozyme). Conclusion. A decrease in the level of mineralizing activity of periodontal bone tissue under conditions of diabetes can be the reason for the development of diabetic periodontitis.